Application of drainage devices in rehabilitation of patients suffering from cystic fibrosis - Czenczek, Ewelina; Lewandowski, Bogumił; Szeliga, Ewa (Polish Journal of Public Health, 2013)
Cystic fibrosis is a chronic and incurable disease, caused by a mutation of a gene, which codes the ionic canal CFTR, which ensures correct hydration of the mucus of the epithelial glands (95% of water in healthy people). In the case a mutation is detected, a considerable concentration of mu-cus occurs in numerous organs of the organism, in particular the respiratory and digestive systems. Applying active techniques of bronchi cleaning with the use of drainage devices constitutes one of the most important elements of comprehensive physiotherapeutic procedure. Nowadays, it is recommended to teach, as early as possible, to practically use drainage devices increasing the expiratory pressure or changing the pressure in the lumen of the bronchial tree, i.e.: PEP mask, Flutter or Acapella. Apart from the high efficiency of the therapy, they provide independent functioning of the patient in social life, without the dependence on people from the outside.